Investigation on Designing and Development of a Selective Laser Melting Manufactured Gas Turbine Blade—Proof-of-Concept - Mihaela Raluca Condruz; Tiberius Florian Frigioescu; Gheorghe Matache; Adina Cristina Toma; Teodor Adrian Badea (Inventions)
In this study, a conceptual turbine blade model with internal cooling channels was designed and fabricated using the selective laser melting (SLM) process. The optimal manufacturing orientation was evaluated through simulations, and the results indicated that vertical orientation yielded the best outcomes, minimizing support material usage and distortion despite increased manufacturing time. Two configurations were produced, namely, an entire-turbine blade model and a cross-sectional model. Non-destructive analyses, including 3D laser scanning for dimensional accuracy, surface roughness measurements, and liquid penetrant testing, were conducted. Visual inspection revealed manufacturing limitations, particularly in the cooling channels at the leading and trailing edges. The trailing edge was too thin to accommodate the 0.5 mm channel diameter, and the channels in the leading edge were undersized and potentially clogged with unmelted powder. The dimensional deviations were within the acceptable limits for the SLM-fabricated metal parts. The surface roughness measurements were aligned with the literature values for metal additive manufacturing. Liquid penetrant testing confirmed the absence of cracks, pores, and lack-of-fusion defects. The SLM is a viable manufacturing process for turbine blades with internal cooling channels; however, significant attention should be paid to the design of additive manufacturing conditions to obtain the best results after manufacturing.